Are traditional birth attendants good for improving maternal and perinatal health? Yes. (14th June 2011) - Ana, Joseph
Abstract : Joseph Ana argues that the shortage of skilled health workers means traditional birth attendants have a valuable place, but Kelsey A Harrison (doi:10.1136/bmj.d3308 ) believes they do more harm than good